Comparison of two nested PCR methods for the detection of human malaria - Anthony, C.; Mahmud, R.; Lau, Y.L.; Syedomar, S.F.; Ponnampalavanar, S.S.L.S. (Malaysian Society of Parasitology and Tropical Medicine, 2013)
Battling malaria will be a persistent struggle without the proper means to diagnose the parasitic infection. However, the inherent limitations of microscopy, the conventional method of diagnosing malaria, affect the accuracy of diagnosis. The present study aimed to compare the accuracy of two different set of primers targeting the small subunit ribosomal RNA (ssRNA) and the dihydrofolate reductase-thymidylate synthase linker region (dhfr-ts) in detecting species specific malaria infections by nested PCR. The sensitivity and specificity of nested PCR assay using the two primers were calculated with reference to microscopy as the gold standard. The results show that 18S rRNA primers had 91.9 sensitivity and 100 specificity in detecting human Plasmodium species as opposed to dhfr-ts primers which had 51.4 sensitivity and 100 specificity. The higher sensitivity of 18S rRNA primers suggests that it may be a better diagnostic tool for detecting human malaria.